Place and Cultural Identity in Joaquin’s The Mass of St. Sylvestre - Mohammad Hossein Abedi Valoojerdi (IAFOR Journal of Arts & Humanities, 2020)
Nick Joaquin (Nicomedes Márquez Joaquín, 1917-2004) is widely known for his interest in the Spanish colonial period and its culture in the Philippines. He employed the “Walled City” or Intramuros (Old Manila) as the setting for "The Mass of St. Sylvestre" (1946) and many other stories. Intramuros not only has an important role in Joaquin’s short story as a physical place, but also conveys identity elements and cultural meanings. This cathedral city has a glorious but neglected past and Joaquin, by retelling the stories from this magnificent past, recalls the link between Filipino identity and the formation of culture during the period of Spanish colonialism. His approach to the issue of identity corresponds to what Stuart Hall classifies as the “Enlightenment Subject” (1996, p. 597). This paper attempts to explore the role that place and the experience of landscape play as markers of cultural identity in "The Mass of St. Sylvestre".